Oestrogen activity of the serum in adolescents with Type 1 diabetes. Issue 10 (12th February 2016) - Martínez, D.; Castro, A.; Merino, P. M.; López, P.; Lardone, M. C.; Iñiguez, G.; Cassorla, F.; Codner, E.
Abstract: Aims: To assess serum oestrogen levels and oestrogenic activity in adolescents with Type 1 diabetes compared with a healthy control group. Methods: We conducted a cross‐sectional study that evaluated adolescents with Type 1 diabetes ( n = 38) and healthy adolescents (control group; n = 32). Serum oestrogens, urinary oestrogen metabolites and serum oestrogenic activity were assessed. Oestrogenic activity was evaluated in an in vitro cell proliferation assay using a modified E‐screen assay with MCF‐7/BUS cells. Results: Adolescents with Type 1 diabetes had lower oestrogenic activity levels in both phases of the menstrual cycle compared with the control group (follicular phase: 76 vs 94%; luteal phase: 97 vs 131%; P < 0.01), even after adjusting for BMI, oestradiol and oestrone levels. Postmenarcheal adolescents with Type 1 diabetes had lower oestradiol levels compared with control subjects in the follicular phase (63.3 pmol/l vs 89.4 pmol/l; P < 0.01) and higher oestrone levels compared with controls in the luteal phase (196 vs 151.9 pmol/l; P < 0.05). Conclusions: Adolescents with Type 1 diabetes had lower levels of serum oestrogenic activity, and these were lower than expected based on their serum oestradiol levels. We postulate that changes in the serum milieu of oestrogens in patients with Type 1 diabetes may explain their decreased oestrogenic activity and may play a role in their adverse metabolic profile. What's new?: Clinical evidence of hypoestrogenism has been found in women with Type 1 diabetes, but there have been no systematic studies evaluating oestrogen profile in such patients. We studied the overall serum oestrogenic activity and oestrogenic profile in adolescents with Type 1 diabetes. This study showed that adolescents with Type 1 diabetes have lower levels of serum oestrogen activity, and these levels were lower than expected based on measurement of their serum oestradiol levels. We postulate that low serum oestrogenic activity levels may play a role in the pathophysiology of chronic complications in women with Type 1 diabetes.